Shadow Economy and a New Quality of De-shadowing Policy Through the Use of Artificial Intelligence Tools - Kraus, Nataliia; Kraus, Kateryna (Herald of Economics, 2026)
The article identifies the actual socio-economic effects of legalization and the threat of shadowing from the use of AI in business and entrepreneurship; to indicate indicators that demonstrate the integration of digital technologies in business for the purpose of transparent business conduct. The state of the shadow economy in the country and the state policy of de-shadowing using AI tools. To achieve the specified goal, the work used methods of analysis and synthesis, grouping, and generalization, which allowed for a comprehensive study of existing scientific achievements on the issues of digital transformation of business using AI, to solve the tasks set for scientists, and to outline the prospects for future research in the area of forming an effective mechanism for the policy of de-shadowing domestic business based on AI tools. The socio-economic benefits of using AI in partial de-shadowing of economic relations are substantiated and indicated, including personalized assistants that reduce the burden on the employee and eliminate the human factor; the ability of AI to protect itself from cyberattacks, that’s, to build a new quality of cyber protection in working with business partners and state institutions. The authors found that with the advent of AI, new challenges arise, such as new tax evasion schemes, i.e., the threat of shadowing economic relations. Scientists argue that the level of shadowing in a country is influenced by institutional capacity. Research has shown that the more software is used, the more likely a company is to eventually use artificial intelligence technologies and use fewer employees. The authors express the opinion that the shadow economy has grown in the last decade due to the emergence of new methods and ways of shadowing economic activity, which were formed on the basis of innovative financial instruments and new generation digital technologies. Prospects for further research include studying the specifics of using AI for the transparency of business process algorithms of digital enterprises, the protection of buyers’ personal data, and the ethics of online trading.